Cracknie, Borgie and the souterrains of the northern mainland of Scotland - Cavers, Graeme; Humble, Jamie; Ritchie, Matt; Humphreys, Paul; Robertson, Jackaline (Proceedings of the Society of Antiquaries of Scotland, 2024)
The souterrains of the northern mainland comprise a distinctive group within the wider national distribution: they are stone-built, narrow with massive lintels and typically associated with hut-circle settlements. Most are known from antiquarian records or from the RCAHMS survey of Sutherland in 1911, and there has been very little investigation of them since; aside from the excavation of an example at Cyderhall Farm in south-east Sutherland and limited investigation at Upper Suisgill, virtually no new data have been contributed since that time. In 2012, Forestry and Land Scotland commissioned the 3D laser scan survey of one example at Cracknie, Borgie, for the purposes of informing conservation management. This led to the excavation of the entrance to the passage and consolidation of the opening in 2022, at which point samples suitable for radiocarbon dating were obtained. These indicate that activity was taking place around the Cracknie souterrain in the early Middle Iron Age, probably around the early 2nd century BC. This paper discusses the Cracknie souterrain in the context of the north mainland group, along with a note on the discovery of a new example at Borgie in 1997, recorded by the late Paul Humphreys, and suggests that the northern stone souterrains should be considered among the earliest such sites to be constructed, and that they probably originated towards the end of the third quarter of the 1st millennium BC. Canmore ID 5765